Sistemas silvopastorales en Portugal: perspectivas para o montado, um sistema multifuncional - PInto-Correia, Teresa (2013)
This lecture adresses the MOntado, its history and its role in the Portuguese landscape and also in the Portuguese agricultral sector. It raises the issue of landscape multifunctionality and how this is understaood and follwoed by land managers.